Carbon Dioxide in Lake Nyos, Cameroon, Estimated Quantitatively From Sound Speed Measurements - Boehrer, Bertram; Saiki, Kazuto; Ohba, Takeshi; Tanyileke, Greg; Rouwet, Dmitri; Kusakabe, Minoru (Frontiers in Earth Science, 2021)
Dissolved gases in the deep water of lakes can be hazardous when extreme concentrations are reached. A sudden release of large amounts of gas can cost the lives of humans living in the neighbourhood, as it has happened at Lake Nyos in 1986. Since 2001, Lake Nyos gas risk has been mitigated by induced degassing, but the connection to the gas source is still in place and a regular survey needs to be implemented to guarantee safe conditions. Frequent sampling at the remote location of Lake Nyos requires an enormous effort and many analytical techniques are nearly impossible to run at the lake site. In this contribution, we combined a commercially available sound speed sensor with a CTD (electrical conductivity, temperature, depth) probe to gain an indirect but quantitative estimate of carbon dioxide concentrations at fine depth resolution (decimetre scale). Dissolved carbon dioxide increases sound speed but does not contribute to electrical conductivity. Hence the difference between measured and calculated (on the base of electrical conductivity, temperature and pressure) sound speed gives a quantitative indication of dissolved carbon dioxide. We highly recommend the implementation of the sound speed-CTD probe combination at Lake Nyos or at other gas-laden volcanic lakes as it could safeguard the people living in the area with acceptable cost and effort for the operators, as alarming CO2 concentrations in deep lake strata will be timely detected.